Modelling damage in fibre-reinforced thermoplastic composite laminates subjected to three-point bend loading. (15th March 2020) - Liu, Haibao; Liu, Jun; Ding, Yuzhe; Zhou, Jin; Kong, Xiangshao; Harper, Lee T.; Blackman, Bamber R.K.; Falzon, Brian G.; Dear, John P.
Abstract: It is important to account for nonlinearity in the deformation of a thermoplastic matrix, as well as fibre fracture and matrix cracking, when predicting progressive failure in unidirectional fibre-reinforced thermoplastic composites. In this research, a new high-fidelity model approach is developed incorporating elastic-plastic nonlinearity. In order to validate the model, three-point bend experiments were performed on composite specimens, with a lay-up of [03 /903 ]2s, to provide experimental results for comparison. Digital Image Correlation (DIC) was employed to record the strain distribution in the composite specimens. The developed intralaminar damage model, which is implemented as a user defined material (VUMAT in Abaqus/Explicit) subroutine, is then combined with a cohesive surface model to simulate three-point bend failure processes. The simulation results, including the load-displacement curves and damage morphology, are compared with the corresponding experimental results to assess the predictive capability of the developed model. Good agreement is achieved between the experimental and numerical results.